2003
DOI: 10.1097/00006324-200311000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Are the Results of the Beery-Buktenica Developmental Test of Visual-Motor Integration and Its Subtests Related to Achievement Test Scores?

Abstract: Visual perceptual ability should be assessed in children with poor math and/or reading achievement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
137
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(162 citation statements)
references
References 9 publications
13
137
1
7
Order By: Relevance
“…Here, VMI does not significantly predict number line estimation anymore. The predictive power of VMI for early arithmetic confirms the findings by Cameron et al (2012) who report that VMI relates to mathematics in kindergarten children (and in older children, see Sortor & Kulp, 2003). We might even suggest that this finding fits with the literature documenting a link between children's finger representation and early mathematics (Fayol, Barrouillet, & Marinthe, 1998;Reeve & Humberstone, 2011).…”
Section: Role Of Different Spatial Measures For Early Mathematicssupporting
confidence: 88%
See 2 more Smart Citations
“…Here, VMI does not significantly predict number line estimation anymore. The predictive power of VMI for early arithmetic confirms the findings by Cameron et al (2012) who report that VMI relates to mathematics in kindergarten children (and in older children, see Sortor & Kulp, 2003). We might even suggest that this finding fits with the literature documenting a link between children's finger representation and early mathematics (Fayol, Barrouillet, & Marinthe, 1998;Reeve & Humberstone, 2011).…”
Section: Role Of Different Spatial Measures For Early Mathematicssupporting
confidence: 88%
“…Moreover, the influence of early VMI for later academic achievement has been empirically supported (Becker, Miao, Duncan, & McClelland, 2014;Cameron et al, 2012Cameron et al, , 2015Carlson, Rowe, & Curby, 2013;Grissmer, Grimm, Aiyer, Murrah, & Steele, 2010). Studies considering VMI and non-motor spatial skills concurrently report that both constructs are associated with and/or are predictive of better performance in mathematics (Carlson et al, 2013;Pieters et al, 2012;Pitchford et al, 2016;Sortor & Kulp, 2003).…”
Section: Link Between Spatial Skills and Early Mathematicsmentioning
confidence: 94%
See 1 more Smart Citation
“…This was previously supported by results showing that visual perception is a good predictor of children's reading level and their readiness to read (e.g., Sortor and Kulp, 2003). Importantly, studies on Semitic scripts showed predictive correlations between both visual and verbal ability and reading.…”
Section: Discussionmentioning
confidence: 56%
“…Görsel algının yazma hızı, kelimeleri doğru kopyalama, kelime ve harfler arasında uygun Ɵekilde boƟluk bırakma, yazma, çizim gibi becerilerde etkili olduğunu belirtilmektedir (Akaroğlu ve Dereli, 2012;Barnhardt, Borsting, Deland, Pham ve Vu, 2005;Christian, 2010;Fletcher, 1997;Gabbard, 2012;Tseng ve Chow, 2000). Barnhardt ve diğerleri (2005), Christian (2010), Kurtz (2006), Sortor ve Kulp (2003) çalÄ±ĆŸmalarında matematiği okuma, matematik iƟaretlerini doğru yazma ve anlama, geometrik Ɵekilleri tanıma, sayıları sıralama, matematik problemlerini organize etme ve problem çözmede görsel algının etkili olduğunu belirtmiƟlerdir.…”
Section: Introductionunclassified